2019
DOI: 10.1051/kmae/2019012
|View full text |Cite
|
Sign up to set email alerts
|

American eel state of buoyancy and barotrauma susceptibility associated with hydroturbine passage

Abstract: American eel are likely to encounter and pass through hydropower turbines, particularly during the downstream spawning migration, where exposure to stressors can potentially lead to injuries and mortality. Previous research has recovered dead eels downstream of hydropower facilities and, for some fish, injuries were easily attributed to blade strike; however, others showed no external signs of injury suggesting that other stressors, such as rapid decompression may be a potential source of mortality. For this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Juvenile American shad tested in this study are also more susceptible to effects of shear and rapid decompression than other fish species, such as silver and yellow phase American eel (Anguilla rostrata), juvenile lamprey (Lampetra spp. ), juvenile rainbow trout (Oncorhynchus mykiss), and a few Australian species, which have been examined similarly [24,30,34,36]. This suggests that measures (i.e., turbine designs or operational modifications) taken to protect juvenile salmonids, or other fish species at hydropower facilities may not be sufficient to protect juvenile American shad.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Juvenile American shad tested in this study are also more susceptible to effects of shear and rapid decompression than other fish species, such as silver and yellow phase American eel (Anguilla rostrata), juvenile lamprey (Lampetra spp. ), juvenile rainbow trout (Oncorhynchus mykiss), and a few Australian species, which have been examined similarly [24,30,34,36]. This suggests that measures (i.e., turbine designs or operational modifications) taken to protect juvenile salmonids, or other fish species at hydropower facilities may not be sufficient to protect juvenile American shad.…”
Section: Discussionmentioning
confidence: 99%
“…Barotrauma injuries can result from gasses expanding within the body (explained by Boyle's Law) or bubble formation in the blood and tissues when gas comes out of solution (explained by Henry's Law) and can vary depending on the operating conditions of the hydropower facility and the species of fish [31,33,35]. Juvenile Chinook salmon (Oncorhynchus tshawytscha) have been observed to sufer mortality at pressure reductions as low as 50% [31], where American eel suffered very few injuries at much greater decompression (≈90% pressure reduction) [36] and lamprey (western brook lamprey, Lampetra planeri and Pacific lamprey, Entosphenus tridentatus) exhibited no physiological or behavioral response to extreme rapid decompression (>90% pressure reduction) [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, Pflugrath et al . () found that eels are not likely to be injured due to rapid pressure changes during downstream migration through hydroturbines.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier publications suggest that the same injury symptoms could be manifested by two different sources and accurate delineation of a cause and effect relationship is difficult (Eicher Associates 1987). However, Pflugrath et al (2019) found that eels are not likely to be injured due to rapid pressure changes during downstream migration through hydroturbines.…”
Section: Classification Of Injury Type On Recaptured Eelmentioning
confidence: 96%
“…During turbine passage, fish are exposed to rapid decompression (Colotelo et al, 2012), which causes an increase in swim bladder volume following Boyle's Law. Therefore, gas exchange in the swim bladder of physoclists is relatively slow and a rapid increase in volume is more likely to result in rupture than physostomous species such as salmonids or cyprinids (Blaxter & Batty, 1990, Boys et al, 2016Beirão et al, 2018;Pflugrath, Boys & Cathers, 2018;Pflugrath et al, 2019). American eel have been found to be exceptionally effective at expelling gas from the swim bladder which resulted in a very low susceptibility to barotrauma (Pflugrath et al, 2019) and this is also likely the case for European eel (Turnpenny et al, 1992).…”
Section: Species Specific Differences and Determination Of Turbine Efmentioning
confidence: 99%